2010
DOI: 10.1007/s00415-010-5759-1
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow abnormalities in patients with neurally mediated syncope

Abstract: The aim of this study is to investigate regional cerebral blood flow (rCBF) in patients with syncope. We compared brain single photon emission computed tomography (SPECT) images of neurally mediated syncope patients with those of age/sex matched healthy volunteers. (99m)Tc-ethylcysteinate dimer (ECD) brain SPECT was performed in 35 patients (M/F = 17/18, mean 36.6 years) with syncope during the asymptomatic period, and in 35 healthy volunteers. For statistical parametric mapping (SPM) analysis, all SPECT image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…36 Apparently, the maximum CBF decreases (76 AE 8%) in microvasculature found in the present study were larger than the maximum drops of mean CBFV (58 AE 14%) 35 or diastolic CBFV (∼40%) 36 in MCA measured by Doppler ultrasound, implying that CBF in small vessels may be more sensitive than CBFV in large vessels for the assessment of VVS. In addition, Joo et al reported that CBF in small vessels of the right prefrontal cortex measured by SPECT during HUT was negatively correlated to the total number of syncopal episodes, 17 which had been demonstrated to be the most powerful predictor of a future syncope. 37 Therefore, CBF measurement holds potential to evaluate the recurrence rate of VVS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…36 Apparently, the maximum CBF decreases (76 AE 8%) in microvasculature found in the present study were larger than the maximum drops of mean CBFV (58 AE 14%) 35 or diastolic CBFV (∼40%) 36 in MCA measured by Doppler ultrasound, implying that CBF in small vessels may be more sensitive than CBFV in large vessels for the assessment of VVS. In addition, Joo et al reported that CBF in small vessels of the right prefrontal cortex measured by SPECT during HUT was negatively correlated to the total number of syncopal episodes, 17 which had been demonstrated to be the most powerful predictor of a future syncope. 37 Therefore, CBF measurement holds potential to evaluate the recurrence rate of VVS.…”
Section: Discussionmentioning
confidence: 99%
“…The right insular cortex is known to be responsible for regulating sympathetic activities such as HR and blood pressure. 10,17 It is possible that reduced CBF in the right insular cortex suppresses sympathetic activities, eventually leading to VVS. 17 As expected, cerebral hypoperfusion (i.e., CBF decline) occurred during presyncope along with cerebral hypoxia (i.e., ½HbO 2 decrease and [Hb] increase).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of interest, a recent study demonstrated cerebral blood flow abnormalities in patients with syncope in their asymptomatic period (i.e., between syncopal attacks). 27 The purpose of this study was to evaluate whether clinical symptoms of ANS dysfunction increase the risk of WMLs, and whether this effect is influenced by the presence of migraine.…”
mentioning
confidence: 99%
“…Studies by using SPECT showed decreases in regional cerebral blood flow in multiple cortical regions, yielding inconsistent results across the studies. [35][36][37] The results of these SPECT studies might be interpreted as a consequence of cerebral hypoperfusion rather than a specific cause of NCS. To our knowledge, there is only 1 exploratory VBM study that showed a reduction of GM volume in the medulla in patients with NCS.…”
Section: Discussionmentioning
confidence: 94%